2018
DOI: 10.3390/nu10020161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Consuming Preloads with Different Energy Density and Taste Quality on Energy Intake and Postprandial Blood Glucose

Abstract: Consumption of reduced energy dense foods and drink has the potential to reduce energy intake and postprandial blood glucose concentrations. In addition, the taste quality of a meal (e.g., sweet or savoury) may play a role in satiation and food intake. The objective of this randomised crossover study was to examine whether energy density and taste quality has an impact on energy intake and postprandial blood glucose response. Using a preload design, participants were asked to consume a sweet (“Cheng Teng”) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…In addition, if the volume of these foods is reduced then this may become obvious, promoting consumer dissatisfaction 166 , and the potential for subsequent compensatory eating to occur 167 . Consistent with this hypothesis, the effect of lower energy density on subsequent food-intake compensation is reduced when visual and sensory cues are removed 168,169 . Therefore, sensory modification may provide a way to reduce energy intake without the need to reduce portion sizespecifically, by lowering energy density, while preserving palatability and by limiting compensatory eating behaviour by maintaining satisfaction.…”
Section: Palatability Food Satisfaction and Expected Satietymentioning
confidence: 60%
“…In addition, if the volume of these foods is reduced then this may become obvious, promoting consumer dissatisfaction 166 , and the potential for subsequent compensatory eating to occur 167 . Consistent with this hypothesis, the effect of lower energy density on subsequent food-intake compensation is reduced when visual and sensory cues are removed 168,169 . Therefore, sensory modification may provide a way to reduce energy intake without the need to reduce portion sizespecifically, by lowering energy density, while preserving palatability and by limiting compensatory eating behaviour by maintaining satisfaction.…”
Section: Palatability Food Satisfaction and Expected Satietymentioning
confidence: 60%
“…A focus on the acute meal effect is important, due to the fact that in the modern world, people are increasingly found to be in a ‘postprandial’ state, resulting from increasing exposure to eating opportunities throughout the day, propagating the effects of western meals on cumulative metabolic trends [222]. Addressing these key related factors has already been shown to favourably affect postprandial outcomes [23,126,215,223,224].…”
Section: Discussionmentioning
confidence: 99%
“…In studies on energy intake and obesity, high-carbohydrate and -fat meals have demonstrated lower satiating effects, leading to overeating, as compared to meals high in innate/added/incorporated water, fibre and protein [21], whereas increased postprandial satiety-per-kilocalorie (kcal) through pre-meal intake of water [22], soups and low-caloric preloads [23,24] reduced intake [25]. Similarly, low-energy density (ED) meals were shown to reduce energy intake during the present and succeeding meal [26], especially if the meal was high-protein (≥25–30 g), which particularly increased specific satiety (per kcal) and reduced energy intake [27].…”
Section: Introductionmentioning
confidence: 99%
“…The time taken to consume the test meal and the liking score of the test meal were recorded for each subject. For the following session, subjects were required to finish the given fruit at minute 0, followed by the test meal at minute 30 [19]. For the last session, the subjects were given their test meals 30 min before the fruit was served.…”
Section: Methodsmentioning
confidence: 99%